Physical education as a way to overcome cultural barriers for foreign students - Novikov, M.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop and test a complex of physical-culture and health-improving measures (team games, tourism, wordless exercises) aimed at removing the language, ethnic, and behavioural barriers of foreign students. Methods and structure of the study. The organisation of the study was carried out under the conditions of the educational process in the discipline “Physical Education” at a higher educational institution. 80 foreign students studying at the university took part in the study. Results and conclusions. In the course of the pedagogical experiment, an assessment was carried out of the effectiveness of the use of team relay races as a means of overcoming cultural barriers in foreign students. The results of the experiment proved the statistically significant advantage of the developed methodology.